Origin and morphology of atypical forms of Streptomyces granaticolor - Stastná, J; Cáslavská, J; Wolf, A; Vinter, V; Mikulík, K (Folia microbiologica, 1977)
Nonfilamentous forms of Streptomyces granaticolor are formed in a medium with amino acids and glucose. They form filaments again after transfer to a medium with glucose and peptone. The nonfilamentous forms do not produce granaticin. Formation of nonfilamentous forms depends on the concentration of the inoculum, on the cultivation temperature and on the presence of simple sugars. Ultrathin sections revealed atypical septation in the nonmycelial forms and non-uniform accumulation of the wall material.
Keywords: Culture Media; Streptomyces; kultivační média